2011
DOI: 10.1039/c0ob01144d
|View full text |Cite
|
Sign up to set email alerts
|

A novel acid-catalyzed C5-alkylation of oxindoles using alcohols

Abstract: A novel C5-alkylation of oxindoles using alcohols as alkylating agents under acid catalysis is described for the first time. The reactions of various benzylic, allylic and propargylic alcohols are studied to obtain the corresponding 5-substituted oxindoles in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Interestingly, the alkylation occurs at C5 and not at C3 (αalkylation) as happens when Lewis acids or basic media are employed [Scheme 20, (a)]. 36 In contrast, the α-alkylation of carbonyl compounds, such as aldehydes, was obtained using PTSA under mild reaction conditions with excellent results especially for (E)-1,3-diphenylprop-2en-1-ol (3) [Scheme 20, (b)]. 37,38 The α-alkylation of various aldehydes using alcohol 3 has been also reported using PTSA (20 mol%) with acetonitrile as the solvent in combination with a polysiloxane (10 mol%) bearing a secondary amine in the structure in a dual activation strategy.…”
Section: Scheme 19 Csp 3 -Csp 2 Bond Formation Catalyzed By Tfohmentioning
confidence: 99%
“…Interestingly, the alkylation occurs at C5 and not at C3 (αalkylation) as happens when Lewis acids or basic media are employed [Scheme 20, (a)]. 36 In contrast, the α-alkylation of carbonyl compounds, such as aldehydes, was obtained using PTSA under mild reaction conditions with excellent results especially for (E)-1,3-diphenylprop-2en-1-ol (3) [Scheme 20, (b)]. 37,38 The α-alkylation of various aldehydes using alcohol 3 has been also reported using PTSA (20 mol%) with acetonitrile as the solvent in combination with a polysiloxane (10 mol%) bearing a secondary amine in the structure in a dual activation strategy.…”
Section: Scheme 19 Csp 3 -Csp 2 Bond Formation Catalyzed By Tfohmentioning
confidence: 99%
“…However, other metal triflates such as Yb(OTf ) 3 , Zn(OTf ) 2 , a Reactions were carried out on a 0.50 mmol of (±)-6a with 0.50 mmol of 7a in 4 mL of solvent. AgOTf, and Sc(OTf ) 3 afforded products in the range of 53-78% isolated yields (entries [8][9][10][11]. Among the various solvents such as dichloroethane, dichloromethane, chloroform, toluene, xylene, acetonitrile, and tetrahydrofuran, it was observed that dichloroethane is a better choice (entries [13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…The combined organic layers were concentrated under reduced pressure. The crude products were purified by column chromatography using a hexane-EtOAc mixture as the eluent to afford the desired product (11).…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing a direct S N 1-like propargylation under mild reaction conditions 34 using readily available propargyl alcohols is a meaningful challenge from the standpoint of reactant compatibility. Many reactant (i.e., secondary alcohols) and nucleophile (arenes, alcohols, thiols, and amides) combinations are incompatible when functional groups are present, such as esters, amides, cyano, and nitro groups.…”
Section: Introductionmentioning
confidence: 99%